Virtual Reality in planning, design, and management of urban green and blue infrastructure - Schewenius, Maria; Wallhagen, Marita (Frontiers in Virtual Reality, 2024)
There is a need for new tools in urban planning, design, and management (urban PDM) of green-blue infrastructure (GBI) to better support resilience and sustainable development. Virtual Reality (VR) emerges as a potential tool in this context. GBI provides a diversity of ecosystem services that increase the capacity of urban environments to absorb change while continuing to develop (adaptive capacity), a key factor in resilience and sustainability. However, there is a lack of tools capable of effectively capturing and communicating the designs, functions, and uses of GBI. Despite this need, research on the contributions of VR as a tool in urban PDM of GBI remains limited. To address this gap, an exploratory experiment using inductive qualitative data analysis was conducted. Participants of different ages and with different expertise viewed 360-degree video clips from urban areas through VR, completed a questionnaire, and participated in interviews. The results showed that the 360-degree video VR experience enhanced participants’ understanding of the viewed sites. Specifically, participants paid attention to details, captured the context, responded by generating emotional engagement, identified site development potential, and described an immersive experience. These results align with key principles for the sustainable management of ecosystem services, such as participation, learning, diversity, place-making, and stewardship; and adaptive capacity aspects such as processes and results grounded in complexity-embracing creativity. Our analysis shows that 360-degree video VR can increase the understanding of complexities, connections, and nuances in the urban environment. We conclude that 360-degree video VR could serve as a valuable complement to traditional tools in urban PDM, enriching decision-making with information that can support adaptive capacity, resilience, and sustainability.